Counsellors in Indian Schools Enabling Optimal Development - Pokhriyal, Shruti; Bhargava, Vinita; Kalra, Mani Bhasin (JOURNAL OF INDIAN EDUCATION, 2022)
Counsellors are important stakeholders in the school community who can significantly influence student mental health and well-being, catering to all students in this regard. With changes occurring in the sociocultural milieu, there is an ever-increasing need for gearing up counselling provisions in indian schools. The article is based on a review of research on counsellors in the school setting, their role, need, barriers and facilitators in the counselling process. Currently, in india, the role of school counsellors is ambiguous, and most schools do not actually have a person functioning in this role. To play a more productive role, counsellors that are in schools must aim to provide comprehensive mental health services. The significance of the Counsellor’s role is gaining momentum in india and there needs to be greater recognition of their likely contributions, for the benefit of students and of society.